Dissecting Amyloid Beta Deposition Using Distinct Strains of the Neurotropic Parasite Toxoplasma gondii as a Novel Tool. (August 2017) - Cabral, Carla M.; McGovern, Kathryn E.; MacDonald, Wes R.; Franco, Jenna; Koshy, Anita A.
Genetic and pathologic data suggest that amyloid beta (Aβ), produced by processing of the amyloid precursor protein, is a major initiator of Alzheimer's disease (AD). To gain new insights into Aβ modulation, we sought to harness the power of the coevolution between the neurotropic parasite Toxoplasma gondii and the mammalian brain. Two prior studies attributed Toxoplasma -associated protection against Aβ to increases in anti-inflammatory cytokines (TGF-β and IL-10) and infiltrating phagocytic monocytes. These studies only used one Toxoplasma strain making it difficult to determine if the noted changes were associated with Aβ protection or simply infection. To address this limitation, we infected a third human amyloid precursor protein AD mouse model (J20) with each of the genetically distinct, canonical strains of Toxoplasma (Type I, Type II, or Type III). We then evaluated the central nervous system (CNS) for Aβ deposition, immune cell responses, global cytokine environment, and parasite burden. We found that only Type II infection was protective against Aβ deposition despite both Type II and Type III strains establishing a chronic CNS infection and inflammatory response. Compared with uninfected and Type I-infected mice, both Type II- and Type III-infected mice showed increased numbers of CNS T cells and microglia and elevated pro-inflammatory cytokines, but neither group showed a >2-fold elevation of TGF-β or IL-10. These data suggest that we can now use our identification of protective (Type II) and nonprotective (Type III) Toxoplasma strains to determine what parasite and host factors are linked to decreased Aβ burden rather than simply with infection.